2004
DOI: 10.1530/eje.0.1510199
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes and impaired glucose tolerance in European children and adolescents with obesity -- a problem that is no longer restricted to minority groups

Abstract: Background: The incidence of childhood obesity and type 2 diabetes is an increasing problem in Europe. We determined the prevalence of impaired glucose regulation in a predominantly Caucasian cohort of 491 children and adolescents with obesity. Methods: Fasting glucose and insulin levels were determined in all 491 subjects. Patients with an abnormal fasting glucose or with additional risk factors (positive family history of type 2 diabetes, acanthosis nigricans, hyperlipidemia; n ¼ 102) underwent an oral gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
100
2
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(126 citation statements)
references
References 39 publications
14
100
2
7
Order By: Relevance
“…The incidence data are scarce, the highest numbers of type 2 diabetes in young adults have been reported in non-Europid ethnic groups [11,21] but the age of diagnosis of type 2 diabetes has decreased also in Europid populations [41,42]. Consistent with these reports, our results indicate that a considerable number of Finnish patients are diagnosed with type 2 diabetes before the age of 40.…”
Section: Discussionsupporting
confidence: 88%
“…The incidence data are scarce, the highest numbers of type 2 diabetes in young adults have been reported in non-Europid ethnic groups [11,21] but the age of diagnosis of type 2 diabetes has decreased also in Europid populations [41,42]. Consistent with these reports, our results indicate that a considerable number of Finnish patients are diagnosed with type 2 diabetes before the age of 40.…”
Section: Discussionsupporting
confidence: 88%
“…Also, Philips et al (17) reported r= 0.55 for the relationship between the insulinogenic index and 3 min insulin level as a measure of first phase insulin during intravenous glucose tolerance test in normoglycemic subjects. Given that the typical sampling times during an OGTT, whether as a clinical or research tool, do not include a 15 minute blood sample (21,22,(24)(25)(26)(27), our findings would suggest that a determination of 15 minute insulin and C-peptide levels may be a better reflection of early phase insulin secretion than the 30 minute. Moreover, because the impairment in first phase insulin secretion is the earliest abnormality in the transition from a normoglycemic state to impaired glucose tolerance/pre diabetes to type 2 diabetes in adults (1,28) and youth (29-31), a 15 minute determination may give a more reliable estimate of changes in first phase insulin secretion in observational or intervention studies.…”
Section: Discussionmentioning
confidence: 94%
“…[4][5][6][7][8] The clinical and metabolic presentation T2DM in Caucasian children differed from the initial reports predominantly of Afro-Americans, Hispanics or Indians. The clinical presentation of 20 European Caucasian children with T2DM is presented in Table 2 and the data concerning the metabolic presentation in Table 3.…”
Section: Clinical Features Of Caucasian Children With T2dmmentioning
confidence: 86%